Butterfly–host plant synchrony determines patterns of host use across years and regions. Issue 4 (8th November 2018) - Toftegaard, Tenna; Posledovich, Diana; Navarro‐Cano, José A.; Wiklund, Christer; Gotthard, Karl; Ehrlén, Johan
Abstract : Variation in the degree of synchrony among host plants and herbivores can disrupt or intensify species interactions, alter the strength of natural selection on traits associated with phenological timing, and drive novel host plant associations. We used field observations from three regions during four seasons to examine how timing of the butterfly herbivore Anthocharis cardamines relative to six host plant species ( Arabis hirsuta, Cardamine pratensis, Arabis glabra, Arabidopsis thaliana, Thlaspi caerulescens and Capsella bursa‐pastoris ) influenced host species use and the choice of host plant individuals within populations. Butterflies laid a larger fraction of their eggs on species that were closer to the butterfly's preferred stage of development than on other host species. Within host plant populations, butterflies showed a stronger preference for individuals with a late phenology when plants within the population were on average more developed at the time of butterfly flight. Our results suggest that changes in synchrony between herbivores and their host plants are associated with changes in both host species use and the choice of host plant individuals differing in phenology within populations. This is likely to be an important mechanism generating variation in interaction intensities and trait selection in the wild, and therefore also relevant for understanding how anthropogenic induced changes, such as global warming, will influence natural communities.